“National” and “Global” Perspectives in the Works of Alexander S. Pushkin - Shirokova, Marina A. (Journal of History Culture and Art Research, 2019)
This paper provides unique perspectives on the place of A. S. Pushkin in vibrant debates between the two key schools of Russian philosophical thought in the 19th century, also known in the scholarship as the “Slavophiles” and “Westernizers.”. In particular, the author considers these schools as ones eventually representing the two key approaches to the development of Russia as a nation. The first approach is built on the uniqueness and national characteristics of Russia’s political and economic development. It perfectly falls within the “Slavophilia” school of thought. The second approach is represented by the group of intellectuals also being called the “Westernizers,” who advocated for the “global” (i.e. “Western”) path in Russia’s development. More than that, the author argues that Alexander Pushkin, a famous a Russian poet and novelist of the Romantic era who lived before the final formation of the two schools, was the pioneer of such both critical perspectives on the “national” and the “global” in Russia’s political and economic development as a nation, which finally became the two central issues of Russian philosophy. The author reviews Pushkin’s focus on the problem of Russia’s role and place in this world, its destiny, as well as the problem of Russia’s necessity to recognize itself as a distinct nation. Relying on scholarly research and documents, the author argues that Pushkin was able to successfully accomplish the “west-eastern synthesis.” In other words, he was superior to the fundamental contradictions existing between the “Slavophiles” and the “Westernizers.” According to the author, Pushkin’s philosophy can be considered not only foundation of both schools, but it actually has the power to bring together both “global” and “national” perspectives on the development of Russia as a nation.